INTEGRASI BUSINESS MODEL CANVAS DENGAN BALANCED SCORECARD PADA USAHA GREEN FOOD DI MARKETPLACE DALAM MENDUKUNG GREEN ECONOMY - I Made Jaya Distira; Ni Luh Indiani; I Gusti Ayu Pradnya Paramitha (Bajang Institute, 2024)
The research objectives are, 1) To find out and analyze the implementation of green food businesses in the marketplace in terms of the business model canvas, 2) To find out and analyze the implementation of green food businesses in the marketplace in terms of the balanced scorecard, 3) To find out and analyze the integration between the business model canvas and balanced scorecard on green food businesses in the marketplace. This research uses this type of research qualitative descriptive through interviews, documentation and literature study. Study This uses a business model canvas. Applying the Business Model Canvas, green food business actors in the marketplace can formulate more targeted and efficient strategies. implementing the Balanced Scorecard, green food businesses in the marketplace can measure and improve performance from various perspectives. The integration between the Business Model Canvas and the Balanced Scorecard in green food businesses in the marketplace allows companies to design effective business models while measuring and monitoring overall performance